The Influence of Promotions on Purchasing Decisions with Brand Image as an Intervening Variable in Chatime Superindo Kedungmundu Products - Mulyani, Endang Dwi; Alim, Muchammad Rully Sjahirul (Economics and Business International Conference Proceeding, 2024)
In the current era of globalization, competition in the business world is very tight. Sales of food and beverages or food industry products are estimated to grow by 5-7% during Ramadhan in 2023. According to the databox survey, the highest sales value by 10 restaurants in Indonesia, especially the Chatime brand, is ranked seventh in Indonesia. This research aims to determine the influence of promotions on purchasing decisions and brand image for Chatime Superindo Kedungmundu products. This research used an accidental sampling technique with a sample size of 100 respondents. The method used in this research is the PLS (Partial Least Square) method using smartPLS software version 4.1. The results of this research show that there is a positive and significant influence between promotion on purchasing decisions through the brand image of Chatime Superindo Kedungmundu products.